Efektivitas Shaping-Token Economy dalam Meningkatkan Motivasi Belajar Anak Tunagrahita Ringan - Siska Ulandara; Marlina Marlina (Jurnal Penelitian Pendidikan Khusus, 2018)
This article contains the results of research on the effectiveness of shaping-token economy in increasing learning motivation of children with intellectual disabilityin class II of SLB Gema Insani Padang. Which is raised from the existing problems in the field, a second grade ofchildren with  intellectual disabilities in SLB Gema Insani Padang who do not have the motivation to learn, especially in terms of working on tasks and activities during the learning hours. This research is a single subject reasearch (SSR) with A-B-A design. The research subjects were mild mentally retarded children with data collection techniques is direct observation. Data were analyzed using graphic visual data analysis techniques. Based on the results of the analysis in conditions and analysis between conditions. This study observed three conditions, namely baseline conditions before intervention (A1), during intervention (B) and baseline after intervention (A2). Stating that mild mental retardation learning motivation increased after intervention. It is proven that Shaping-token economy is effective in improving the learning motivation of children with intellectual disability. So the teacher can apply the shaping-token economy technique in classroom learning.